Acute Appendicitis in a Patient with Systemic Lupus Erythematosus - Hendra Gunawan; Awalia Awalia; Joewono Soeroso (Interna Publishing, 2019)
Systemic lupus erythematosus (SLE) is a chronic excacerbative autoimmune disease with wide clinical spectrum. Gastrointestinal manifestasion is a frequent clinical manifestasion seen in SLE. Management with glucocorticoid and non-steroid anti-inflammatory drugs (NSAID) can mask the gastrointestinal symptoms in patient with SLE. One of the etiologies of gastrointestinal manifestations in SLE is acute appendicitis. Patients with acute appendicitis usually have abdominal pain as its chief complaint. The pathophysiology of acute appendicitis can occur primarily from SLE and secondary from other causes eg: infection, inflammation, etc. When a SLE patient has acute appendicitis as its initial assessment, determining its etiology is pivotal to give comprehensive management and preventing life-threatening complications.